(3OjhGf GdbWjajs - (3eMeO Hf eGd Gddg GdehShj GdNWj, GdbWjajs
(3ChdgG (B:s
(3GdMO ddg GdPj CfWb HGdTYQ dSGf UajI BOe CHj GdHTQ, hYdeg GdLeY Hjf QKGA GHfg gGHjd EP bJdg bGHjd hNdO aj SbQ hHjf EHGfg Cf GdYGde JYJQjg MhGOK GdZjQ s
(3BNQgG (B:s
(3GdQcI jJSdi HgG GdaDGO GdTLj s
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B181 s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHIBjI Gddg GdMcje GdYGeI HGdfLa (B(758) s
Keywords: (3GdCOHs